(3GdeSjM GdeNdU ai GdeUGOQ GdjghOjI hGdeSjMjIs ((3eY efGXQI OjfjI Hjf jghOi heSjMi CeGe Gdedc Ohf CdahfUh edc GdHQJZGd SHW jghOG(B)s - (3GdZfOhQ, fHjd CfSis ((3GdLjRI, eUQs (3ecJHI GdfGaPIs, 2007)
(3GdcJGH jYWjfG fHPI Yf GdYbjOI GdjghOjI hfHPI Yf GdYbjOI GdeSjMjI ceG jJfGhd acQI GdeSjM GdeNdU YfO GdjghO heGgjI GdeSjM GdeNdU ai GdeUGOQ GdeSjMjI ceG jbOe GdcJGH efGXQI cHQi Hjf GdOjGfJjfs
(3jTJed Ydi UaMGJ HGddZI GdYHQjIs
(3jTJed Ydi bGFeI HGdeUGOQ hGdeQGLYs
Hurg
5
Keywords: (3GdOjGfGJ GdebGQfIs; (3GdeSjMjI hGdjghOjIs; (3GdeSjMjIs; (3GdjghOjIs